2017
DOI: 10.1089/jpm.2016.0235
|View full text |Cite
|
Sign up to set email alerts
|

Bereavement Service Preferences of Surviving Family Members: Variation among Next of Kin with Depression and Complicated Grief

Abstract: Findings indicate a difference in the projected service use of the bereaved experiencing depression and/or complicated grief. Follow-up screenings 6-12 months post-bereavement are recommended to identify those in need of formal psychosocial support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Even though few relationships and differences turned out to be significant, we need to be careful in interpreting any (lack of) differences in psychosocial functioning related to aspects of cremation in terms of causality. The study by Banyasz et al (2017) on the use of bereavement-related services more generally is illustrative. Persons with depression and complicated grief reported greater willingness to use specific services such as a memorial website than those without.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though few relationships and differences turned out to be significant, we need to be careful in interpreting any (lack of) differences in psychosocial functioning related to aspects of cremation in terms of causality. The study by Banyasz et al (2017) on the use of bereavement-related services more generally is illustrative. Persons with depression and complicated grief reported greater willingness to use specific services such as a memorial website than those without.…”
Section: Discussionmentioning
confidence: 99%
“…O'Rourke et al (2011) conducted a large empirical study which identified a number of predictors of satisfaction with funerals (e.g., religiosity). Of similar interest, Banyasz et al (2017) looked into preferences for bereavement services, finding some differences in association with depression or complicated grief among the family members. In a small study, covering various durations of bereavement, Rugg and Jones (2019) examined what mattered to the bereaved regarding funerals.…”
Section: Review Of Scientific Studies Of Funeral Practices and Griefmentioning
confidence: 99%
“…Most attended therapy or support groups and thought it should be a routine component in bereavement. This finding is supported by others who found individual counselling and support groups to be one of the bereavement services that were the most helpful and useful in families' grief processes . One option for ICUs to consider is to provide resources to families on how to find counselling services in their communities, especially if the hospital serves a wide geographic area.…”
Section: Discussionmentioning
confidence: 71%
“…Finally, memorial services have been identified as ritual practices that can be helpful . However, most of the families in our study would not have attended a memorial service if offered by either the ICU or the hospital.…”
Section: Discussionmentioning
confidence: 98%
“…Bereavement services that target the time surrounding the death, such as viewing the body, providing information on the funeral, and making referrals, are more established than those services that follow bereaved family members over time, which is consistent with other surveys. 12,14,15,19,21 Nurses provide these immediate services more often than physicians do, and acute care health professionals more often than their colleagues in psychiatric settings. This is not surprising given nurses' mandate to care for the dying and their family members.…”
Section: Discussionmentioning
confidence: 99%